Real-Time Resonance Detection and Active Damping in Energy Recovery Railways Applications - Giovanni Marini; Alessandro Lidozzi; Marco di Benedetto; M. Moranchel Perez; Luca Solero (IEEE Open Journal of the Industrial Electronics Society)
This article presents a real-time active damping methodology for front-end inverters connected to the railway catenary in energy recovery applications. The system arrangement comprises a three-phase 2.5 MW inverter connected to the ac grid with a suitable filter. On the opposite side it shares the dc-side with the railway plant where traction inverters and auxiliary systems are connected. The proposed method tries to solve a problem when the energy recovery converter, operating with an almost constant power load, stimulates the catenary power line. This method estimates the dc-side resonant frequency, isolates the dc voltage oscillations around the resonant frequency, and finally attenuates the related effects by acting on the inverter current control strategy. Experimental tests are shown to validate the method using the hardware-in-the-loop real-time emulator. Thanks to the HIL, the complete catenary system has been modeled according to the real data provided by the train operator. The control algorithm and the related control board have the same structure as the architecture used in the field. The results show the effectiveness of the proposed method in detecting the resonance and reducing its effects, increasing the catenary robustness, and making the proper integration of energy recovery systems possible.